Potentialities and critical issues of liquid biopsy in clinical practice: An umbrella review - Nicola Veronese; Claudio Luchini; Stefano Ciriminna; Katia Spinelli; Santo Fruscione; Paola Mattiolo; Miriam Belluzzo; Veronica Messina; Lee Smith; Mario Barbagallo; Walter Mazzucco (Translational Oncology)
Background: Liquid biopsy (LB) is a laboratory test performed on a fluid sample aiming at analyzing molecular data derived from circulating cells and related entities, or from nucleic acids. This umbrella review aims to map and evaluate the evidence supporting the use of LB in medicine across different medical specialities and conditions. Methods: We searched three repositories from database inception up to October 1, 2023 and we included meta-analyses of observational studies reporting data on the use of LB, compared to gold standard, and its accuracy (area under the curve, AUC). Results: Among 726 articles initially screened, 42 systematic reviews were included. Most of the outcomes explored (202/211) were related to cancer. We found that 75/211 had an excellent accuracy (AUC >0.90), with one comparison with an AUC equal to 1, i.e., Cell-Free Human Papillomavirus DNA (cfHPV-DNA) for HPV-positive oropharyngeal squamous cell carcinoma. However, considering published meta-analyses, all the outcomes were graded as very low on the GRADE criteria, and the heterogeneity was never reported. Discussion: The literature about LB is rapidly increasing and some promising data about precision oncology are now available. However, this umbrella review on existing meta-analyses highlighted some critical issues for providing quantitative estimations on the different roles of LB.